Empowering communities through IoT-enabled fish cultivation in Kembangarum Subdistrict, Semarang City - Rizky Muliani Dwi Ujianti; Noora Qotrun Nada; Slamet Budirahardjo; Mohamad Fajarianditya Nugroho; Setyoningsih Wibowo; Mutiara Fitri Rahmaningtyas; Nurul Hidayah; Yanuar Noor Wicaksono; Aldo Kamadi (Universitas Muhammadiyah Magelang, 2024)
This community service activity aims to improve the welfare of the people of Kembangarum Subdistrict, Semarang, through the development of catfish cultivation based on Internet of Things (IoT) technology. The implementation of the activity includes needs analysis, pond construction, IoT installation, training, and assistance in fish cultivation and post-harvest processing. The results of the activity show an increase in community understanding of IoT technology and its application in catfish cultivation. Additionally, a grant was provided in the form of a catfish pond equipped with an IoT system for real-time water quality monitoring. This activity also successfully improved community skills in processing harvested fish into various products, thus potentially increasing community income. Overall, this community service activity has contributed to the development of the local economy and opened up opportunities for the formation of a thematic catfish village in Kembangarum Subdistrict.